Unveiling the Drivers of Polio Vaccine Uptake: Insights from a Multi-Country Study of 37 Nations in Sub-Saharan Africa - Getayeneh Antehunegn Tesema; Michael Sarfo; Sylvester R. Okeke; Edward Kwabena Ameyaw; Sanni Yaya (PLoS ONE, 2025)
Background Childhood vaccination is a highly cost-effective strategy for preventing vaccine-preventable diseases, including poliomyelitis. Despite advancements in vaccination coverage across Africa, polio remains a public health concern. Limited multi-country analyses on oral polio vaccine (OPV) dropout in African nations hinder the development of context-specific interventions. This study investigates OPV uptake and associated factors in sub-Saharan Africa (SSA). Methods This study analyzed data from the Demographic and Health Surveys of 37 sub-Saharan African countries, encompassing 60,846 children aged 12–23 months. Multilevel multinomial logistic regression models were employed to explore associations between individual- and community-level factors and vaccination status, categorized as non-vaccinated, dropout, or fully vaccinated. Four nested models were assessed, with the model exhibiting the lowest deviance (-2 Log-likelihood Ratio (-2LLR)) identified as the best fit. Variables with p-values <  0.2 in bivariable analysis were included in the multivariable analysis. The adjusted Relative Risk Ratios (aRRR) with 95% Confidence Intervals (CI) were reported to determine statistical significance and the strength of associations. Results Among children aged 12–23 months, OPV1, OPV2, and OPV3 coverage rates were 86.59%, 81.27%, and 68.41%, respectively. The prevalence of OPV dropout and full vaccination in SSA were 19.38% (95% CI: 19.06%, 19.69%) and 67.77% (95% CI: 67.40%, 68.14%), respectively, with a dropout rate of 20.98%. Key factors significantly associated with non-vaccination included maternal education (primary: aRRR =  0.58; secondary: aRRR =  0.64; higher: aRRR =  0.75), household wealth (poorer: aRRR =  0.91; middle: aRRR =  0.82; richer: aRRR =  0.70), maternal age (20–29: aRRR =  0.67; 30–39: aRRR =  0.60; 40–49: aRRR =  0.59), health facility delivery (aRRR =  0.28), media exposure (aRRR =  0.64), marital status (currently married: aRRR =  0.87), parity (2–3 births: aRRR =  1.11), and rural residence (aRRR =  0.73). Regional disparities revealed higher risks of non-vaccination and dropout in Southern, Central, and West Africa compared to East Africa. Conclusion This study highlights the multifaceted determinants of oral polio vaccination dropout in SSA. Targeted interventions, such as improving maternal education, enhancing access to healthcare facilities, addressing socioeconomic inequalities, and mitigating regional disparities, are essential to boosting vaccination coverage and preventing polio resurgence. Focused efforts in Western and Central Africa are critical to sustaining and expanding vaccination programs.